Association between burnout syndrome and anxiety in residents and anesthesiologists of the Federal District - Govêia,Catia Sousa (2018)
Abstract Background and objective There is a shortage of studies addressing the association between burnout syndrome and anxiety among anesthesiologists. Identifying the relationship between these two conditions is of fundamental importance for the prevention, follow-up, and treatment of the professionals. Thus, we evaluated the association between burnout syndrome and anxiety in anesthesiologists and residents of anesthesiology in the Federal District. Method A cross-sectional study using a convenience sample of residents and anesthesiologists from the Federal District. The correlation between State Trait Anxiety Inventory and Burnout Syndrome (Maslach Burnout Inventory) was tested using multiple linear regression analysis, considering a significance level of 5%. Results Of the 78 completed forms, there were predominance of males (57.69%), mean age of 42 ± 9.7 years for anesthesiologists and 30 ± 2.9 years for residents. Burnout syndrome had a prevalence of 2.43% among anesthesiologists and 2.70% among resident physicians, while a high risk for its manifestation was 21.95% in anesthesiologists and 29.72% in resident physicians. There was a correlation between state-anxiety and the variables burnout emotional exhaustion, burnout depersonalization, and trait-anxiety. Regarding trait-anxiety, there was no statistically significant correlation with other variables. Conclusions There is association between state-anxiety and the emotional exhaustion dimensions of burnout, burnout depersonalization, and trait-anxiety. The occurrence of anxiety can negatively influence the way the individual faces daily stressors, which may be related to the use of ineffective strategies to cope with stress.